HALAL SKINCARE PRODUCT EDUCATION FOR STUDENTS AS MUSLIM CONSUMERS AT MA’HAD AL-JAMI’AH UIN K.H. ABDURRAHMAN WAHID PEKALONGAN - Rahma Dwi Amalia; Dina Khitrotul Hawa; Damayanti; Lintang Ayu Wulandari; Alfi Ilmiyatun Nafisah; Hendry Hermawan Adinugraha; Ade Gunawan (Amala Jurnal Pengabdian Kepada Masyarakat, 2025)
This service focuses on increasing the awareness and understanding of Ma'had Al-Jami’ah UIN K.H. Abdurrahman Wahid Pekalongan students on the importance of choosing halal skincare products as part of their responsibility as Muslim consumers. The main objective of this activity is to provide education on the concept, characteristics, and identification of halal skincare products so that students do not only follow viral cosmetic trends, but also pay attention to aspects of Sharia in the use of personal care products. The implementation method consists of counseling with a participatory approach, starting with a pre-test to measure the initial knowledge of the participants, the delivery of material by resource persons through active discussions, to evaluating understanding at the end of the activity. The results of the activity showed an increase in participants' awareness in distinguishing halal and non-halal products, as well as an increased interest in paying attention to labels and distribution permits when buying skincare. Although the activity ran effectively, the limited presentation tools were a challenge in delivering the material. However, the enthusiasm of the participants and active involvement during the discussion are indicators of the success of this program. In the future, it is hoped that similar activities can be carried out in a sustainable manner with the support of digital media in order to reach a wider audience and shape consumptive behavior that is in line with sharia values.